Changing Antimicrobial Resistance Trends in Kathmandu, Nepal: A 23-Year Retrospective Analysis of Bacteraemia - Zellweger, Raphaël M.; Basnyat, Buddha; Shrestha, Poojan; Prajapati, Krishna G.; Dongol, Sabina; Sharma, Paban K.; Koirala, Samir; Darton, Thomas C.; Boinett, Christine; Thompson, Corinne N.; Thwaites, Guy E.; Baker, Stephen; et al. (Frontiers in Medicine, 2018)
A comprehensive longitudinal understanding of the changing epidemiology of the agents causing bacteraemia and their AMR profiles in key locations is crucial for assessing the progression and magnitude of the global AMR crisis. We performed a retrospective analysis of routine microbiological data from April 1992 to December 2014, studying the time trends of non-Salmonella associated bacteraemia at a single Kathmandu healthcare facility. The distribution of aetiological agents, their antimicrobial susceptibility profiles, and the hospital ward of isolation were assessed. 224,741 blood cultures were performed over the study period, of which, 30,353 (13.5%) exhibited growth for non-contaminant bacteria. We observed a significant increasing trend in the proportion of MDR non-Salmonella Enterobacteriaceae (p<0.001), other Gram-negative organisms (p=0.006), and Gram-positive organisms (p=0.006) over time. Additionally, there was an annual increasing trend in the proportion of MDR organisms in bacteria-positive blood cultures originating from patients attending the emergency ward (p=0.006) and the outpatient department (p=0.006). This unique dataset demonstrates that community acquired non-Salmonella bacteraemia has become an increasingly important cause of hospital admission in Kathmandu. An increasing burden of bacteraemia associated with MDR organisms in the community underscores the need for preventing the circulation of MDR bacteria within the local population.